African Diaspora Protection: Amulets in New Spain, New Granada, and the Caribbean - Andrea Guerrero Mosquera (Anuario Colombiano de Historia Social y de la Cultura, 2023)
Objective: To underline that beyond the territories under Portuguese rule, evidence of the use of protective amulets can also be found in places under Hispanic control and the Caribbean. This study aims to enrich historiography on the subject and dialogue with it regarding source analysis and a rereading based on the descriptions of central-western Africa from the sixteenth to the eighteenth century. Methodology: It interrogates sources widely used for the study of African matrix cultures in America from a different perspective and reviews non-written sources that allow visualizing written ones in their context. Originality: This paper contributes to the understanding of how sources can be reread to research African Diaspora cultures in the light of their connected history, tracing the use of these amulets in specific socio-cultural contexts. Conclusions: By considering and interrogating diverse sources on the conversion of Africans and the African diaspora in the Americas, these stories transcend the immutable benevolence of Catholicism and Eurocentrism and question the myopia of the Jesuits and inquisitors in New Spain and New Granada when observing African customs.